Control of pig reproduction - Cole, D. J. A.; Foxcroft, G. R. (Butterworths, 1982)
Control of Pig Reproduction focuses on carefully evaluated techniques and technologies involved in the control of pig reproduction. The selection first ponders on the sexual development of male pigs, including early fetal, perinatal, and pubertal periods. The text also discusses testicular steroids and boar taint; interrelationships between spermatozoa, female reproductive tract, and egg investments; and artificial insemination. Discussions focus on androgens, estrogens, deposition of semen and uterine transit, sperm regulation and release by the isthmus, and types of artificial insemination.